2016
DOI: 10.1109/tnet.2015.2434217
|View full text |Cite
|
Sign up to set email alerts
|

A General Privacy-Preserving Auction Mechanism for Secondary Spectrum Markets

Abstract: Auctions are among the best-known market-based tools to solve the problem of dynamic spectrum redistribution. In recent years, a good number of strategy-proof auction mechanisms have been proposed to improve spectrum utilization and to prevent market manipulation. However, the issue of privacy preservation in spectrum auctions remains open. On the one hand, truthful bidding reveals bidders' private valuations of the spectrum. On the other hand, coverage/interference areas of the bidders may be revealed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…However, the Boneh-Goh-Nissim (BGN) cryptosystem involving the bilinear map and bilinear group [118] was used instead of the OPE to map and encrypt the bids. The simulation results in [117] showed that the satisfaction ratio, i.e., the percentage of winning bidders, of the proposed scheme can reach to one with the small number of bidders, i.e., less than 200. However, there is no numerical experiment to show the performance improvement related to the strategy-proofness as well as the privacy preserving.…”
Section: Grouping Results Grouping Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the Boneh-Goh-Nissim (BGN) cryptosystem involving the bilinear map and bilinear group [118] was used instead of the OPE to map and encrypt the bids. The simulation results in [117] showed that the satisfaction ratio, i.e., the percentage of winning bidders, of the proposed scheme can reach to one with the small number of bidders, i.e., less than 200. However, there is no numerical experiment to show the performance improvement related to the strategy-proofness as well as the privacy preserving.…”
Section: Grouping Results Grouping Resultsmentioning
confidence: 97%
“…By selecting the smallest bid as the representation bid of a non-conflict group, the approach in [117] allows the bidders in the group to receive more benefit since they only pay less price than their expected bids. However, such a low price causes a loss in revenue for the seller.…”
Section: Grouping Results Grouping Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Countermeasure solutions for these attacks have also been proposed, ranging from introducing randomness to multihop path selection [178], [179] to making the source nodes move randomly [8] to confuse the attackers. Unlike other wireless systems, location privacy preservation that addresses vulnerabilities in CRN s has not, however, received much attention, though several works related to spectrum sensing [11], [54], [55], [72], [180]- [182], spectrum auction bids [155], [183], subscriber identification [184], and database-driven DSA [54], [55], [180]- [182], [185] have been proposed.…”
Section: Limitations Of Generic Privacy Enhancingmentioning
confidence: 99%
“…Based on RSA, Juels and Szydlo proposed a privacy preserving auction mechanism with a reasonable computational complexity [41]. Specific to online applications, a number of auction mechanisms [20,21,25] get a good tradeoff between performance and security. Unfortunately, these works only consider bid protection, but ignore the problem of verification.…”
Section: Related Workmentioning
confidence: 99%